Juvenile hormone pathway in honey bee larvae: A source of possible signal molecules for the reproductive behavior of Varroa destructor. Issue 2 (21st December 2020) - Aurori, Cristian M.; Giurgiu, Alexandru‐Ioan; Conlon, Benjamin H.; Kastally, Chedly; Dezmirean, Daniel S.; Routtu, Jarkko; Aurori, Adriana
Abstract: The parasitic mite Varroa destructor devastates honey bee ( Apis mellifera ) colonies around the world. Entering a brood cell shortly before capping, the Varroa mother feeds on the honey bee larvae. The hormones 20‐hydroxyecdysone (20E) and juvenile hormone (JH), acquired from the host, have been considered to play a key role in initiating Varroa's reproductive cycle. This study focuses on differential expression of the genes involved in the biosynthesis of JH and ecdysone at six time points during the first 30 hr after cell capping in both drone and worker larvae of A. mellifera . This time frame, covering the conclusion of the honey bee brood cell invasion and the start of Varroa's ovogenesis, is critical to the successful initiation of a reproductive cycle. Our findings support a later activation of the ecdysteroid cascade in honey bee drones compared to worker larvae, which could account for the increased egg production of Varroa in A. mellifera drone cells. The JH pathway was generally downregulated confirming its activity is antagonistic to the ecdysteroid pathway during the larva development. Nevertheless, the genes involved in JH synthesis revealed an increased expression in drones. The upregulation of jhamt gene involved in methyl farnesoate (MF) synthesis came into attention since the MF is not only a precursor of JH but it is also an insect pheromone in its own right as well as JH‐like hormone in Acari. This could indicate a possible kairomone effect of MF for attracting the mites into the drone brood cells, along with its potential involvement in ovogenesis after the cell capping, stimulating Varroa's initiation of egg laying. Abstract : In an effort to answer a long‐standing question on how hormonal interactions in the honey bee larvae can sustain the parasite Varroa destructor reproduction, the current study focused on differential expression analysis of the genes involved in the Juvenile hormone (JH) and ecdysteroid associated pathways. All the results were discussed considering the V. destructor related reproductive behavior. The results revealed the higher expression in drones relative to workers for the jhamt gene involved in methyl farnesoate (MF) synthesis. MF is the precursor of JH, also an insect pheromone and the JH‐like hormone in Acari. These results suggest a possible kairomone effect of MF for attracting the mites into the drone brood cells, along with its potential involvement in ovogenesis after the cell sealing, stimulating Varroa's fertility.